Agonist‐induced desensitisation of β3‐adrenoceptors: Where, when, and how?. (7th April 2019) - Okeke, Katerina; Angers, Stephane; Bouvier, Michel; Michel, Martin C.
Abstract : β3 ‐Adrenoceptor agonists have proven useful in the treatment of overactive bladder syndrome, but it is not known whether their efficacy during chronic administration may be limited by receptor‐induced desensitisation. Whereas the β2 ‐adrenoceptor has phosphorylation sites that are important for desensitisation, the β3 ‐adrenoceptor lacks these; therefore, it had been assumed that β3 ‐adrenoceptors are largely resistant to agonist‐induced desensitisation. While all direct comparative studies demonstrate that β3 ‐adrenoceptors are less susceptible to desensitisation than β2 ‐adrenoceptors, desensitisation of β3 ‐adrenoceptors has been observed in many models and treatment settings. Chimeric β2 ‐ and β3 ‐adrenoceptors have demonstrated that the C‐terminal tail of the receptor plays an important role in the relative resistance to desensitisation but is not the only relevant factor. While the evidence from some models, such as transfected CHO cells, is inconsistent, it appears that desensitisation is observed more often after long‐term (hours to days) than short‐term (minutes to hours) agonist exposure. When it occurs, desensitisation of β3 ‐adrenoceptors can involve multiple levels including down‐regulation of its mRNA and the receptor protein and alterations in post‐receptor signalling events. The relative contributions of these mechanistic factors apparently depend on the cell type under investigation. Which if any of these factors is applicable to the human urinary bladder remains to be determined. Linked Articles: This article is part of a themed section on Adrenoceptors—New Roles for Old Players. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.14/issuetoc